Life Quality of Older People Receiving Institutional Care - Burzyńska, Monika; Pikala, Małgorzata; Kondak, Katarzyna; Maniecka-Bryla, Irena (Acta Universitatis Lodziensis. Folia Oeconomica, 2017)
In the modern world there is a growing number of older people with decreasing the possibility of taking care of them at the same time. This situation is mainly caused by family demographic changes. The aim of the study was to evaluate the quality of life of older people receiving institutional care. The survey was conducted from April to June 2015 after obtaining the consent of the Bioethics Committee of the Medical University of Lodz. The studied population consisted of residents of 5 nursing homes in the province of Lodz randomly selected for the study. Hodgkinson Abbreviated Mental Test Score was used to assess the mental state of respondents. Finally statistical analysis covered 117 people. Research tool was an anonymous interview questionnaire (49 questions on lifestyle, family relationships, self‑assessment of health status and quality of life). The obtained data was entered into the database in Microsoft Excel and Statistica. In statistical analysis descriptive and analytical statistics were used. To determine the relationship between the analyzed variables and self‑reported quality of life Chi² test (p < 0.05) was used. 62.1% of respondents declared poor self‑assesment of quality of life – more often women (Chi² = 0.919). 69.2% of seniors declared dependent on the decision to live in nursing home. Factors associated with self‑rated quality of life of respondents were: the time of the placement at nursing home, frequency of meetings with the family, the result of ADL scale and self‑rated health. Taking care of family relationships affects the quality of life of seniors living in nursing homes. Migration of young people limits the possibility of providing support to seniors by the family, leading to increased involvement of the institutional support to the elderly.